PREVALENCE OF PATIENT'S FAMILY STRESS IN HOSPITAL INCLUSION DURING THE COVID-19 PANDEMIC - Indriyani, Indriyani; Andas, Amzal (Nursing Genius Journal, 2024)
Background Of Study : A study has shown that hospitalized patients are more susceptible to psychological stress than others and family members with previous treatment experience have higher psychological distress. The impact felt by the family on the first day in the inpatient room is experiencing anxiety, fear, sleep disturbances and can cause stress. This study aims to determine the description of family stress in the Inpatient Room during the COVID-19 pandemic. Methods:This research is descriptive analytic by using a cross sectional approach. The number of research samples was 54 families of patients who were treated in the Inpatient Room at Izza Cikampek Hospital. The sampling technique used consecutive sampling. The data analysis technique used univariate analysis. Results:This study showed that the majority of respondents experienced moderate stress as many as many as 21 people (38.9%), 20 people did not have stress (37.0%), 11 people mild stress (20.4%) and 2 people (3.7%). Conclusion: The average patient's family in the Inpatient Room at Izza Cikampek Hospital experienced stress, with moderate stress being dominated. Conclusion: It is hoped that the family can reduce the triggering factors for stress and the Hospital Agencies improve the quality of services and facilities so that families are more comfortable when accompanying patients.